Trauma, Rememory and Language in Holodomor Survivors’ Narratives - Лариса Засєкіна (Психолінгвістика, 2020)
The objective of the research is to examine language use in Holodomor survivors ‘narratives as psycholinguistic markers of mental trauma and PTSD. The specific objective is to explore rememory as a cognitive strategy of releasing suppressed traumatic events.